Pengaruh Lingkungan Kerja Dan Kompetensi Karyawan Terhadap Kinerja Karyawan Pada PT Sarana Majukan Ekonomi Finance Indonesia - Gaby Cynthia Dewi; Slamet Heri Winarno (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2024)
This scientific work aims to determine whether or not there is an influence between the work environment and employee competence on employee performance at PT Sarana Majukan Ekonomi Finance Indonesia using quantitative statistical research methods. Data collection was carried out in 3 (three) ways, namely observation, documentation study, and questionnaire. The researcher used a purposive sampling method and from the results of the Slovin formula calculation, it was obtained that the number of samples to be studied was 29 respondents. This research uses several tests, namely the data quality test, classical assumption test, hypothesis test, and finally the coefficient of determination test (R2). Based on the discussion of the research results, it can be concluded that the work environment has a partial or separate significant effect on employee performance at PT Sarana Majukan Ekonomi Finance Indonesia, employee competency has no partial or separate significant effect on employee performance at PT Sarana Majukan Ekonomi Finance Indonesia, and the work environment and employee competency has a significant effect simultaneously or together on employee performance at PT Sarana Majukan Ekonomi Finance Indonesia. A comfortable and safe work environment and good employee competence can realize employee performance as expected by the company.